Fantastic poetry in Mexico: three nocturnes by Xavier Villaurrutia - Márquez Ayala, Alexis (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This article is a fantastic reading of three nocturnes by the Mexican poet Xavier Villaurrutia. Through some guidelines of the author’s poetics, a link is established with the definitions of the theory of the fantastic, essentially based on the idea of ​​confrontation between the real and the impossible. This link is described in the three selected poems (“Nocturno en que habla la muerte”, “Nocturno miedo” and “Nocturno en que nada se oye”), which involve different modes and levels of manifestation of the fantastic system. Finally, through the analysis of the poems, a broader exploration of Mexican fantastic poetry is suggested, regarding a couple of examples.